Electrode processes in electrolysis of zirconium at production of plastic zirconium for nuclear energy - Mukhachev, A.P.; Nefedov, V.G.; Kharytonova, O.A. (Вопросы атомной науки и техники, 2019)
The analysis of the conditions for industrial production of zirconium by the electrolysis of a melt of potassium fluorozirconate and potassium chloride in a sealed electrolyzer with a current load of 10 kA was carried out. It is shown that the developed method of preparing the raw material without the use of chlorine, with electrolytic reduction of zirconium provides the production of a metal of nuclear purity, with a hafnium content of less than 0.005 wt.% polyvalent ion electrodes. The current output of zirconium is 55...60%, which may be due to reversible oxidation-reduction on the electrodes of polyvalent ions. The low resistance of the graphite anode is due to both chemical interaction with the released fluorine and chlorine, and its mechanical destruction. Проведено аналіз умов промислового отримання цирконію електролізом розплаву фторцірконата калію і хлориду калію в герметичному електролізері зі струмовим навантаженням 10 кА. Показано, що розроблений метод підготовки сировини без застосування хлору з електролітичним відновленням цирконію забезпечує отримання металу ядерної чистоти з вмістом гафнію, менш 0,005 мас.%. Вихід по струму цирконію становить 55…60%, що може бути пов'язано з оборотним окисленням-відновленням на електродах полівалентних іонів. Невисока стійкість графітового анода обумовлена як хімічною взаємодією з фтором і хлором які виділяються, так і механічним його руйнуванням. Проведен анализ условий промышленного получения циркония электролизом расплава фторцирконата калия и хлорида калия в герметичном электролизере с токовой нагрузкой 10 кА. Показано, что разработанный метод подготовки сырья без применения хлора с электролитическим восстановлением циркония обеспечивает получение металла ядерной чистоты с содержанием гафния менее 0,005 мас.%. Выход по току циркония составляет 55…60%, что может быть связано с обратимым окислениемвосстановлением на электродах поливалентных ионов. Невысокая стойкость графитового анода обусловлена как химическим взаимодействием с выделяющимися фтором и хлором, так и механическим его разрушением.